Desain Low Power Node dan Timer Dengan Atmega328p Berbasis NRF24l01 - Tantri Isworo T. R. P.; Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The data transmission process in the technology sector is increasingly being applied wirelessly. A wireless data transmission architecture that is often implemented is called the Wireless Sensor Network (WSN). In solving certain problems, wireless data transmission is carried out continuously so that it requires large amounts of electricity. In addition, the mechanism for making alternative data transmission lines is needed when data transmission through the main line is experiencing problems. This mechanism is needed so that data transmission is not interrupted even though the main transmission line cannot be used. But solutions using these mechanisms have the consequence of increasing the required electrical power. Another solution offered in this study is to enable sleep mode with a low power node design so that power consumption is focused on the data transmission path that is being used. The design of this solution utilizes nRF24L01-based Atmega328P microcontroller which activates one of the transmission lines that are to be used and deactivates (sleep mode) on the transmission line that is not being used. According to the results of experiments that have been carried out, the average value of the electric current when applying sleep mode is 60.45182 mA and electrical power is 5.44 watts. This value is smaller than a system without sleep mode that requires 73.38182 electric current and 6.6 watts of electric power. This proves that the proposed method was successful in reducing electricity consumption.